Projekt historii wizualnej - Skotarczak, Dorota (Slavia Occidentalis, 2011)
The article discusses the relations between history and the diversified audiovisual sphere. It presents the project of visual history which may be defined as a multi-disciplinary research subfield dealing with the analysis of (audio)visual performances in a historical context. In this understanding, visual history comprises all spheres that appear on the junction of history/historiography, photography, film, visual arts, new media and all visualisations of the past and of historical knowledge. Its tasks, on the one hand, consist in stressing the role of (audio)visual performances in creating historical performances (imageries about the past) and thus becoming a specific alternative for academic historiography. However, on the other hand, visual history brings forth the research methods useful for making analyses of audiovisual representations of the past as relatively new and equal to written history and historical sources, requiring new skills from a historian in the field of criticism and hermeneutics of media communications.